2021
DOI: 10.1109/jstars.2021.3059991
|View full text |Cite
|
Sign up to set email alerts
|

Bridging a Gap in SAR-ATR: Training on Fully Synthetic and Testing on Measured Data

Abstract: Obtaining measured Synthetic Aperture Radar (SAR) data for training Automatic Target Recognition (ATR) models can be too expensive (in terms of time and money) and complex of a process in many situations. In response, researchers have developed methods for creating synthetic SAR data for targets using electromagnetic prediction software, which is then used to enrich an existing measured training dataset. However, this approach relies on the availability of some amount of measured data. In this work, we focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 22 publications
1
55
0
1
Order By: Relevance
“…As observed in [52], [6], [28], using an adversarial maximizer in the DNN's training objective can significantly improve the robustness and quality of learned representations in SAR-ATR models. Inkawhich et al [28] directly found that this modification also leads to sizable gains in OOD detection performance.…”
Section: Detecting Anomalous Sar Targetsmentioning
confidence: 95%
See 4 more Smart Citations
“…As observed in [52], [6], [28], using an adversarial maximizer in the DNN's training objective can significantly improve the robustness and quality of learned representations in SAR-ATR models. Inkawhich et al [28] directly found that this modification also leads to sizable gains in OOD detection performance.…”
Section: Detecting Anomalous Sar Targetsmentioning
confidence: 95%
“…Previous work has shown that when the majority of the training distribution is measured, the detection problem for the SAMPLE dataset is nearly solved [28]. However, it is also shown that at K = 0, OOD detection of the SAMPLE-Holdout classes is particularly difficult because there is a distribution gap between the training and test sets that is the result of inaccuracies in the complex SAR simulation process [6]. For this reason, we focus on the K = 0 setting in our SAR-ATR experiments.…”
Section: B Automatic Target Recognition In Sar Imagerymentioning
confidence: 99%
See 3 more Smart Citations